The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1051/0004-6361/202039737
|View full text |Cite
|
Sign up to set email alerts
|

Small Solar System objects on highly inclined orbits

Abstract: Context. Less than one percent of the discovered small Solar System objects have highly inclined orbits (i > 60°), and revolve around the Sun on near-polar or retrograde orbits. The origin and evolutionary history of these objects are not yet clear. Aims. In this work we study the surface properties and orbital dynamics of selected high-inclination objects. Methods. BVRI photometric observations were performed in 2019–2020 using the 2.0 m telescope at the Terskol Observatory and the 2.6 m telescope at the C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 64 publications
3
12
2
Order By: Relevance
“…Both observing runs were conducted under clear (sky 90% cloudless at elevation >30°, transmission variation <10%) or photometric (sky cloudless, transmission variation <2%) conditions as defined by ESO; as a result, we expect the continuum colors of our spectra to be minimally affected by clouds, and therefore accurate. As in previously reported observational epochs (Kiss et al 2013;Szabó et al 2018;Hromakina et al 2021), 2012 DR 30 was found to be inactive both times we observed it.…”
Section: Observationssupporting
confidence: 90%
See 3 more Smart Citations
“…Both observing runs were conducted under clear (sky 90% cloudless at elevation >30°, transmission variation <10%) or photometric (sky cloudless, transmission variation <2%) conditions as defined by ESO; as a result, we expect the continuum colors of our spectra to be minimally affected by clouds, and therefore accurate. As in previously reported observational epochs (Kiss et al 2013;Szabó et al 2018;Hromakina et al 2021), 2012 DR 30 was found to be inactive both times we observed it.…”
Section: Observationssupporting
confidence: 90%
“…In Figure 2 we present our optical reflectance spectra of 2012 DR 30 in comparison to all published optical photometric and spectroscopic reflectance data where such data cover 0.6 μm, enabling consistent scaling between data sets (literature data sets include those reported by Kiss et al 2013;Szabó et al 2018;Hromakina et al 2021). Optical photometric colors were converted to coarse reflectance spectra using methods described by Hainaut & Delsanti (2002) and were scaled relative to the reflectance value at 0.6 μm on a line drawn between the two data points on either side of that wavelength.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The data obtained with reprocessed observations of asteroids for this long-term period are highly useful for a more detailed study of the dynamics and modern orbital parameters of asteroids (see, for example, Savanevych et al 2015;Savanevych et al 2018;Hromakina et al 2021;Vavilova et al 2022) as well as the obtained photometric parameters are very complementary with present-day data for studying changes in brightness and light curves (see, for example, Marzari, 2020).…”
Section: Discussionmentioning
confidence: 93%